Pengaruh Metode Discovery terhadap Prestasi Analogi Matematis Peserta Didik SMKN 1 Sakra - Sulhiah Sulhiah (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2019)
The research uses factorial design, aims to find out the effect of discovery method on the analogy achievement and mathematical generalization of students of SMKN 1 Sakra. The population of this study was all students of SMKN 1 Sakra, and the research sample was taken using the Cluster Random Sampling technique, namely by looking for class XII students, two classes to be sampled. This study consisted of two groups, namely learning the discovery method and the expository method. Class XII.A was made as an experimental group, while class XII.B was made as a control group. Each class consists of 36 students who are divided into three different abilities of students, namely high achievers, medium achievers and low grade students. Research data were collected through tests, questionnaires, observations and interviews. The results of this study are an increase in the ability of mathematical analogies of students who obtain learning using the discovery method better than students who obtain the expository method.